When is the trend the cycle? - Dan Vu Cao; Jean-Paul L'Huillier; Donghoon Yoo (Osaka University, Institute of Social and Economic Research (ISER), 2022)
A literature debates the explanations for the cyclical properties of emerging markets using either trend shocks (Aguiar and Gopinath 2007) or financial frictions (Neumeyer and Perri 2004; Garcia-Cicco, Pancrazi, and Uribe 2010). We state a formal proposition that makes explicit the parametric assumptions needed for consumption to behave (exactly) as in a random-walk, permanent income model. The result is general and applies to economies with endogenous investment and production. The proposition offers a fresh perspective on the debate regarding the sources of emerging market fluctuations, and reconciles diverging findings in the literature. Moreover, we quantitatively explore the business cycle properties of the RBC model when one moves away from the parametric assumptions suggested by the proposition.
Keywords: E21; E27; E32; 330; Aggregate productivity; permanent income; trend